(Watch my moves) [compact disc] - Vile, Kurt (Verve Records, 2022)
On his first album in partnership with Verve Records, Kurt Vile pulls his talents as a singer, songwriter, multi-instrumentalist, and producer in unexpected directions, and the result is a vibrant yet meditative record propelled by laid-back charm and a curious spirit.